PENGGUNAAN KATA SAPAAN DALAM RANAH KESANTUNAN BERBAHASA PADA MASYARAKAT JAWA DESA LANGKANG LAMA KECAMATANPULAU LAUT TIMUR KABUPATEN KOTABARU - SRI JUNIATI (STKIP Paris Barantai, 2017)
The purpose of this study is (1) to know the types of greetings in the field of language politeness in the community of Java Village Langkang Lama Kecamatan Pulau Laut TimurKabupaten Kotabaru, (2) to know the use of the word greeting in the field of language politeness in the community of Java Langkang Lama Village Kecamatan Pulau Laut Timur of Kabupaten Kotabaru, (3) to know the Public Communication by using the word greeting in the sphere of politeness language in the community of Java Langkang Lama Village, Kecamatan Pulau Laut Timur, KabupatenKotabaru. The method used in this research is descriptive qualitative research methods that describe the objective and actual stages of the at the time of communication. While this type of research is a case study in which the study is about an activity of a society that aims to understand the object being studied. The result of the research shows that (1) The use of the word greeting in the Speech Language Speech in Java Community Langkang Lama Subdistrict of Pulau Laut Timur Kabupaten Kotabaru there are 3 types of greeting that is greeting the name of self, greeting kinship and greeting non-kinship, (2) Use of Greeting in sphere Speech Language used by the Community of Java Langkang Lama Village District of Pulau Laut Timur Kabupaten Kotabaru is the use by self-name, the use of kinship greeting consists of mbah lanang, mbah wedok, pak'e, mak'e, kakang, iyu, adek, call the name, adek, name, thole, ndok, pak'de, bu'de, pak'lek and bu'lek. The use of non-friendship greeting consists of mbah, mbah, pak'lek, bu'lek, kakang, iyu, name, mention name, adek, adek, pak lurah and pak RT. And (3) Community Communication by Using Greeting Speech in Speech Language Speech in Java Community Langkang Lama Kecamatan Pulau Laut Timur Kabupaten Kotabaru using two types of Java language, the Ngoko Java language and Javanese Krama. Keywords: Greetings, Speech Language and Java Society.